(untitled) (Raparin Journal of Humanities (RJH), 2022)
Since the name ’Hobbes’ in one way or another, associated with political philosophy and the problem of power in particular, rarely comes to mind, he focused on ’religion’ as a sensitive and crucial subject in political matters. The prevailing view is that it deals with the issue of power in the first place. However, if we look closely at his texts, we find a major component in his philosophical thought, which is; ’Religion’. Religion as an epistemological problem and as a political problem cannot be overcome without solving it in the political space. Because wars and political instability are often due to rivalries and conflict between religious sects and internal wars, Hobbes believes that the radical solution is based on a new organization of the relationship of religion to power. Rarely did researchers analyze the concept of religion, the motives of religiosity and its relationship to power and knowledge. Therefore, the research answers the following question: Are Hobbes’ criticisms of religion and its call for absolute power, the ultimate goal and ultimate end of it? or the end is; Coexistence between religions and sects and political and social stability? From here, the research tries to prove: that his criticisms of the sects and religious rivalries were for that goal. The mental assumption of instability and chaos, which he calls the ’natural state’, and the transition from a state of ’war of all against all’ to stability can only take place through a social contract that guarantees coexistence and ensures that ’power’ is delegated to a higher authority only. Absolute power is a means, not an end in itself. So, the coexistence between the different components of society under one roof is the framework that guides Hobbes’ thought. Key words: Aristotle, religion, opposition to authorities, stability, politics.